(untitled) (International Journal of Engineering and Computer Science, 2014)
In an industrial plant, physical process systems consist of machines and process equipment. They are individual devices or larger subsystems of their own. Process systems can be in different operational states, such as ‘maintenance’, ‘starting up’ or ‘operating’. In each state, they provide a set of capabilities that can be combined to perform the various stages of the process. In the course of control system design, control tasks identified in co-operation with users and other engineering disciplines are allocated to the control system and human operators. The automated parts should form a structured set of control activities corresponding to the physical equipment and processing tasks. In this paper we are implementing CAN and ZigBee networks based Industrial monitoring and control applications on ARM. The ARM Microcontroller having two interconnected CAN interfaces with advanced acceptance filters. The system consists of 4 sub systems. The sub systems one and two acts as sensor nodes. These node are acquire the sensor information, process the data and transmitting the through the CAN bus to third Sub system. The third subsystem based the LPC2129 which receives the data from the sensor nodes and processes the data, transmitted this data to central receiver node via wireless ZigBee communication. The Subsystem four is the central receiver systems which can collect the data from the node receiver unit and transmitted this data to data logging sever.